Engineering response to climate change - Watts, Robert G (Boca Raton : CRC Press, Taylor & Francis, 2013)
'PREFACE In June 1991, we convened the Workshop on the Engineering Response to Global Climate Change: Planning a Research and Development Agenda. Approximately 70 scientists and engineers spent 4 days discussing what research was necessary in order to identify the causes and the extent of climatic change, to assess its consequences, and to prepare for mitigative and adaptive measures. Seven working groups were established: Sources and Sinks of Greenhouse Gases; Energy Demand, Energy Supply; Agricultural and Biological Systems; Water Resources; Coastal Hazards; and Geo-engineering. Each working group was asked to identify a set of goals and a set of approaches to accomplish these goals. Common goals and approaches were then identified, and small, interdisciplinary groups were convened to expand upon the various approaches. Some chapters of the present book are updates of chapters from the book Engineering Response to Global Climate Change that was published in 1997. However, in a real sense it is a new book. Several chapters introduce new material. Even so, the general idea is the same: the climate/energy problem has become largely an engineering problem. The book is more about what we as engineers can do to prevent, mitigate, or adapt to climate change'--
Revised edition of: Engineering response to global climate change. 1997.
Includes bibliographical references and index.
Keywords: Climatic changes -- Environmental aspects; Environmental engineering -- Environmental aspects; Ecological engineering; Global environmental change; Greenhouse gases -- Environmental aspects